Item-Level Story Recall Predictors of Amyloid-Beta in Late Middle-Aged Adults at Increased Risk for Alzheimer’s Disease - Mueller, Kimberly D.; Du, Lianlian; Bruno, Davide; Betthauser, Tobey; Christian, Bradley; Johnson, Sterling; Hermann, Bruce; Koscik, Rebecca Langhough (Frontiers in Psychology, 2022)
Background: Story recall (SR) tests have shown sensitivity to rate of cognitive decline in individuals with Alzheimer’s disease (AD) biomarkers. Although SR tasks are typically scored by obtaining a sum of items recalled, item-level analyses may provide additional sensitivity to change and AD processes. Here we examined the difficulty and discrimination indices of each item from the Logical Memory (LM) SR task, and determined if these metrics differed by recall conditions, story version (A vs. B), lexical categories, serial position, and amyloid status. Methods: n=1141 participants from the Wisconsin Registry for Alzheimer’s Prevention longitudinal study who had item-level data were included in these analyses, as well as a subset of n=338 who also had amyloid PET imaging. LM data were categorized into 4 lexical categories (proper names, verbs, numbers, and ‘other’), and by serial position (primacy, middle, and recency). We calculated difficulty and discriminability/memorability by item, category, and serial position and ran separate repeated measures ANOVAs for each recall condition, lexical category, and serial position. For the subset with amyloid imaging, we used a two-sample t-test to examine whether amyloid positive (A+) and amyloid negative (A-) groups differed in difficulty or discrimination for the same summary metrics. Results: In the larger sample, items were more difficult (less memorable) in the delayed recall condition across both story A and story B. Item discrimination was higher at delayed than immediate recall, and proper names had better discrimination than any of the other lexical categories or serial position groups. In the subsample with amyloid PET imaging, proper names were more difficult for A+ than A-; items in the verb and ‘other’ lexical categories and all serial positions from delayed recall were more discriminate for the A+ group compared to the A- group. Conclusion: This study provides empirical evidence that both LM stories are effective at discriminating ability levels and amyloid status, and that individual items vary in difficulty and discrimination by amyloid status, while total scores do not. These results can be informative for the future development of sensitive tasks or composite scores for early detection of cognitive decline.